Eulerian-lagrangian simulations of unsteady gas-liquid flows in bubble columns - Buwa, Vivek V.; Deo, Dhanannjay S.; Ranade, Vivek V. (International Journal of Multiphase Flow, 2006)
We studied the dynamics of gas-liquid flows in a rectangular bubble column using Eulerian-Lagrangian simulations. Three-dimensional, unsteady simulations were performed to simulate the dynamic characteristics of the oscillating bubble plume. The effect of superficial gas velocity and aerated liquid height-to-column width (HI K) ratio on the dynamic and time-averaged flow properties was studied and the simulated results were validated using wall pressure and voidage fluctuation measurements. The effect of lift force and numerical diffusion on the dynamic and time-averaged properties is discussed in detail. Further, the results obtained using the Eulerian-Lagrangian simulations were compared with the Eulerian-Eulerian simulations. The bubble scale information, which is otherwise lost in the Eulerian-Eulerian simulations, was validated using the voidage fluctuation measurements. Such experimentally validated Eulerian-Lagrangian models will be useful for the simulation of mass transfer and reactions in bubble columns. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Bubble column; CFD; Dynamics; Eulerian-Eulerian simulations; Eulerian-Lagrangian simulations; gas-liquid flow

Structure determination and dynamics of protein-RNA complexes by NMR spectroscopy - Dominguez, Cyril; Schubert, Mario; Duss, Olivier; Ravindranathan, Sapna; Allain, Frederic H. T. (Progress in Nuclear Magnetic Resonance Spectroscopy, 2011)
Keywords: Dynamics; NMR spectroscopy; Protein-RNA complex; Structure determination

Capillary uptake in macroporous compressible sponges - Chatterjee, Soumyajyoti; Doshi, Pankaj; Kumaraswamy, Guruswamy (Soft Matter, 2017)
The capillarity-driven uptake of liquid in swellable, highly porous sponges is of significant industrial importance. Sponges prepared using polymers and their composites with carbon nanotubes and graphene have been reported, with extraordinary solvent uptake capacities and with the ability to separate oil from water. However, the effect of systematic variation of sponge characteristics on solvent uptake has not been investigated. Here, we report experiments that study capillary uptake in a variety of flexible, centimetre-sized macroporous cylindrical sponges. We used ice-templating to prepare a series of model macroporous sponges in which the porosity, modulus and composition were systematically varied. We investigated two kinds of sponge: (a) those composed purely of cross-linked polymers and (b) those prepared as composites of inorganic particles and polymers. Both kinds of sponge are flexible and exhibit elastic recovery after large compressive deformation. All sponges were characterized thoroughly with respect to their pore microstructure and elastic modulus. When one end of a sponge is plunged into a large reservoir, water rises through capillary action against gravity. We observed a transition from an inertial capillary regime, where the liquid column height rose linearly with time, t, to a viscous capillary regime, where the liquid height rose with time t(0.5). We showed that these results can be rationalized using analyses developed for rigid sponges. We combined differential momentum balance equations for uptake in rigid capillaries with the phenomenological Ergun-Forchheimer relations to account for the effect of the sponge microstructure. This approach works remarkably well in the viscous capillary regime and shows that capillary uptake is governed primarily by the total porosity and pore dimensions of soft sponges.
Keywords: aerogels; Building blocks; Catalyst Supports; Contact-angels; Dynamics; flow; Organic Liquids; Porous-Media; Rise

Studies on the role of unsaturation in the fatty acid surfactant molecule on the thermal conductivity of magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (Journal of colloid and interface science, 2017)
To study the role of unsaturation in the surfactant molecule on the thermal conductivity of magnetite nanofluids, four different fatty acid (stearic, oleic, linoleic, and linolenic acids with different degree of unsaturation) coated magnetite nanoparticles of comparable size are prepared and dispersed in toluene. It is found that the nanofluid with the saturated fatty acid coated nanoparticles show larger viscosity than the fluid with the unsaturated fatty acid coated particles at all concentrations. Thermal conductivity studies show enhancement only above a critical concentration for all fluids. The critical concentration for thermal conductivity enhancement varies with the surfactant, possibly due to the difference in the degree of aggregation of the nanoparticles in the fluid, because of the difference in the conformation of the surfactant molecules on the nanoparticle's surface. The experimental thermal conductivity follows the Maxwell model at higher concentrations. From the overall studies, it is observed that the thermal conductivity of the fluids with aggregated or assembled nanoparticles shows slightly larger enhancement than that of the fluids with isolated particles. However, in the presence of a magnetic field, the fluids with isolated nanoparticles showed relatively larger enhancement, possibly due to the easy response of the isolated magnetite nanoparticles to the applied field. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Chains; Dynamics; Enhancement; Fields; Fluids; Forces; gold nanoparticles; Magnetic fluid; Nanofluid; Surfactant; Unsaturation; Conformation; Thermal conductivity; Viscosity; Self-assembled Monolayers

Steric and electronic effect in unsymmetrical squaraine dyes for dye-sensitized solar cells - Nawghare, Indrajeet S.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of physical chemistry C, 2023)
Functionalizing the light harvesting sensitizers with additional electron-donating or -withdrawing groups is a potential approach to modulate the photophysical and electrochemical properties which in-turn optimizes the driving force associated with the charge injection and dye-regeneration processes at the dye-TiO2/electrolyte interface and the photovoltaic device performance in dye-sensitized solar cells (DSSCs). Furthermore, modulated electronic levels of the dyes provide an opportunity to reduce the overpotential associated with the dye-regeneration process and make the dye-TiO2 interface compatible with various electrolytes. Furthermore, an in-built steric feature by means of introducing linear/branched alkyl groups in the sensitizer is important in controlling the aggregation of dyes on the TiO2 surface. Hence, to integrate both steric and electronic properties, a series of alkyl group-wrapped unsymmetrical squaraine dyes (SQ-X) with electron-donating and -withdrawing groups have been designed, synthesized, and utilized for DSSC device fabrication. These dyes are functionalized with alkyl groups at both sp(3)-C and N-atoms of the indoline donor moiety at the nonanchoring side to have a similar steric feature. Photophysical and electrochemical studies revealed that the HOMO and LUMO energy levels of the SQ-X series of dyes have been modulated systematically with sufficient driving forces for both charge injection and dye-regeneration processes with iodolyte (I-/I-3(-)) electrolyte. In the presence of electron-donating groups in SQ-X (where X = -NPh2 and -OMe), the HOMO energy levels are less positive than SQ-H, whereas the presence of electron-withdrawing groups such as -CO2Me, -CN, and -NO2 pushed the HOMO energy levels toward more positive potentials. Enhanced photovoltaic performances have been obtained for the dyes containing electron-donating groups, where the dye with the -NPh2 group showed a maximum of eta 7.03% (V-OC 708 mV, J(SC) 13.16 mA cm(-2), and ff 78%). The dye with the strong electron-withdrawing group -NO2 showed an efficiency of 1.49% (V-OC = 634 mV, J(SC) = 3.13 mA cm(-2), and ff 75%). As the dyes with the electron-withdrawing group possess deep positive HOMO energy levels, the DSSC device characterization has been investigated with the Cu+/2+ redox shuttle. The reduced device performance of electron-withdrawing-group-containing dyes is due to the unfavored charge distribution in the LUMO compared to the presence of electron-donating-group-containing dyes, and it was supported by the difference in the charge injection efficiency.
Keywords: cobalt; Donor; Dynamics; Organic dyes

DNA-mediated formation of phase-separated coacervates of the nucleic acid-binding domain of TAR DNA-binding protein (TDP-43) prevents its amyloid-like misfolding - Patni, Divya; Patil, Anjali D.; Kirmire, Mona S.; Jha, Anjali; Jha, Santosh Kumar (ACS Chemical Neuroscience, 2024)
Sequestration of protein molecules and nucleic acids to stress granules is one of the most promising strategies that cells employ to protect themselves from stress. In vitro, studies suggest that the nucleic acid-binding domain of TDP-43 (TDP-43tRRM) undergoes amyloid-like aggregation to beta-sheet-rich structures in low pH stress. In contrast, we observed that the TDP-43tRRM undergoes complex coacervation in the presence of ssDNA to a dense and light phase, preventing its amyloid-like aggregation. The soluble light phase consists of monomeric native-like TDP-43tRRM. The microscopic data suggest that the dense phase consists of spherical coacervates with limited internal dynamics. We performed multiparametric analysis by employing various biophysical techniques and found that complex coacervation depends on the concentration and ratio of the participating biomolecules and is driven by multivalent interactions. The modulation of these forces due to environmental conditions or disease mutations regulates the extent of coacervation, and the weakening of interactions between TDP-43tRRM and ssDNA leads to amyloid-like aggregation of TDP-43tRRM. Our results highlight a competition among the native state, amyloid-like aggregates, and complex coacervates tuned by various environmental factors. Together, our results illuminate an alternate function of TDP-43tRRM in response to pH stress in the presence of the ssDNA.
Keywords: amyloid-likeaggregation; complex coacervation; DNA-protein interactions; Dynamics; pH stress; TDP-43

Viscosity effects on the dynamics of diols and diol-based deep eutectic solvents - Chatterjee, Srijan; Deshmukh, Samadhan H.; Chowdhury, Tubai; Bagchi, Sayan (Photochemistry and Photobiology, 2024)
Diols, characterized by the presence of two hydroxyl groups, form extended hydrogen-bonded networks. Increasing hydrocarbon chain length is known to elevate the viscosity of diols. Given the established influence of viscosity on solvent dynamics, it becomes imperative to comprehend the impact of viscosity on the fluctuation dynamics within diols and establish connections with hydrogen bond formation and breaking dynamics. In this study, we employ two-dimensional infrared spectroscopy to investigate the viscosity dependence of the structural evolution dynamics in three diols with varying chain lengths. Complementing our experimental approach, molecular dynamics simulations are conducted to extract hydrogen bond lifetimes. Our findings reveal a linear correlation between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. Notably, the selected diols exhibit the capability to form deep eutectic solvents upon mixing with choline chloride at specific molar ratios. In contrast to molecular solvents like diols, deep eutectic solvents are characterized by the formation of heterogeneous nanodomains, comprising various intercomponent hydrogen-bonded networks. Interestingly, our observations indicate that while the fluctuation dynamics decelerate with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is not linear, in contrast to the observed linearity in diols. This nuanced understanding contributes to the broader comprehension of the interplay between viscosity and dynamics in both molecular and deep eutectic solvents. We investigate the impact of viscosity on structural evolution dynamics in diols with varying chain lengths. Employing two-dimensional infrared spectroscopy and molecular dynamics simulations, we explore the relationship between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. We report a linear correlation in diols between viscosity, fluctuation timescales, and hydrogen bond lifetimes. Diols also form deep eutectic solvents, characterized by heterogeneous nanodomains. While fluctuation dynamics slow down with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is nonlinear, contrasting with diols' linearity. This understanding enhances comprehension of viscosity-dynamics interplay in molecular and deep eutectic solvents.image
Keywords: Dynamics; Hydrogen bond; solvent; spectroscopy; viscosity